A 3D aligning method for stimulated emission depletion microscopy using fluorescence lifetime distribution. Issue 11 (11th August 2014) - Wang, Yifan; Kuang, Cuifang; Li, Shuai; Hao, Xiang; Xu, Yingke; Liu, Xu
ABSTRACT Optimal resolution by stimulated emission depletion (STED) microscopy requires precise alignment of the donut‐shaped depletion focus to the excitation focus. In this article, we demonstrate that fluorescence lifetime distribution can be implemented to align the STED system. Different from the traditional aligning methods in which a scattering imaging module is often equipped, the lifetime‐based method is free from probable mismatches between the scattering mode and the fluorescent mode, drift errors caused by separate imaging and complex fitting methods. Based on this method, a spatial resolution of 38 nm by time‐gated detection has been achieved. Microsc. Res. Tech. 77:935–940, 2014. © 2014 Wiley Periodicals, Inc.